ENGLISH LANGUAGE TEACHING STRATEGY FOR ASD (AUTISM SPECTRUM DISORDER) STUDENTS - LASINTIA, MIFTA; PRIHANTORO, PRIHANTORO; EDY, SARWO; ARIANI, DESTI (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2021)
This study aimed at investigating the realization of English language teaching strategies for Autism Spectrum Disorder (ASD) students, especially in terms of the implementation of teaching strategies. This study took place at SMPLB of Curup, Bengkulu, Indonesia. Drawing upon a constructivist epistemology, this study applied a descriptive qualitative method to reveal the data. There was only one English teacher who taught ASD students, and the teacher was involved as the subject of this study. The data were garnered form interviews and document analysis. The data were further analyzed using an interactive model extending to data collection, data condensation, data display, and drawing conclusions. The results showed that the teacher used three strategies in teaching children with autism, namely developing oral language comprehension, echolalia, and communication skills enhancement through the PECS method. In addition, the teacher also modified the form of the strategy according to the needs of students with autism.